Covalent cross-linked aramid nanofiber aerogel film as well as preparation method and application thereof

Through the preparation method of covalent crosslinked aramid nanofiber aerogel film, the problem of structural collapse of polymer nanofiber aerogel at high temperature is solved, and its mechanical properties and deformation ability are significantly improved.

CN119505351APending Publication Date: 2025-02-25TIANJIN POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669939.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing polymer nanofiber aerogels are prone to structural collapse at high temperatures, which limits their application in the field of high temperatures.

Method used

Covalently crosslinked by mixing the aramid nanofiber sol with halogenated alkanes to form a pre-crosslinked ANF, and then treated with scraping film, acid solidification bath and water bath, and finally a covalent crosslinked aramid nanofiber aerogel film was obtained by solvent replacement and freeze-drying.

Benefits of technology

The mechanical properties of the aerogel film are improved, and the crosslinked nanofiber stack forms dense pore walls, which improves fracture strength and deformation ability, while increasing toughness and significantly improving fracture energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505351A_ABST
    Figure CN119505351A_ABST
Patent Text Reader

Abstract

The invention discloses a covalent cross-linked aramid nanofiber aerogel film as well as a preparation method and application thereof, and belongs to the technical field of thermal insulation materials and thermal insulation materials. The preparation method comprises the following steps: mixing aramid nanofiber sol and halogenated hydrocarbon, then carrying out covalent cross-linking, and then carrying out membrane scraping treatment, acid coagulation bath and water bath treatment to obtain a wet gel membrane; and then carrying out solvent replacement and drying to obtain the covalent cross-linked aramid nanofiber aerogel film. The mechanical property of the prepared CCAAM is effectively improved, nanofibers formed by crosslinking are stacked to form a compact hole wall, the breaking strength is improved, a hierarchical hole nanofiber skeleton honeycomb enables the CCAAM to have more deformability, the strain is improved, and meanwhile, the crosslinked aerogel film is effectively toughened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation materials and heat insulating materials, and in particular relates to a covalently cross-linked aramid nanofiber aerogel film and a preparation method and application thereof. Background Art

[0002] In the face of high-temperature dynamic complex insulation scenarios, it is crucial to develop high-performance thermal protection materials. At present, a variety of materials with significant insulation and flame retardant properties have been developed, such as mineral wool, glass fiber, polymer-based foam, and inorganic / organic aerogels. Among these materials, nanoporous aerogels have attracted much attention due to their high porosity, large specific surface area, low apparent density and low thermal conductivity, and are regarded as one of the most promising insulation materials. Inorganic aerogels, especially silicon-based aerogels, have long been favored by researchers for their high porosity and low density, and are widely used in the field of thermal insulation. However, the brittleness, low mechanical strength and poor elasticity of silicon-based aerogels greatly limit their extensiveness in practical applications. In comparison, organic aerogels show higher toughness and flexibility, especially in the field of dynamic insulation. Among them, polymer nanofiber aerogels with nanofibers as structural units have a three-dimensional network structure formed by chemical crosslinking or physical entanglement. While maintaining high porosity and low density, they have many advantages such as high flexibility, high elasticity and easy molding. Therefore, they have great application potential in the field of next-generation flexible insulation materials. However, current polymer nanofiber aerogels are prone to structural collapse at high temperatures, limiting their application in high-temperature fields.

[0003] Aramid nanofibers (ANFs) have attracted extensive attention from researchers due to their unique one-dimensional nanoscale size, high aspect ratio, high specific surface area, excellent mechanical properties, good heat resistance and high chemical thermal stability. ANFs sol can be easily converted into aerogels through the sol-gel method to form a three-dimensional nanofiber network with high porosity. However, the mechanical properties of self-supporting ANF aerogels are relatively low at present, and the porosity will be lost when improving them through densification lamination methods, which greatly limits their application in practical scenarios.

[0004] Therefore, there is an urgent need for a method to improve the mechanical properties of aramid nanofiber aerogels to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a covalently cross-linked aramid nanofiber aerogel membrane and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a covalently cross-linked aramid nanofiber aerogel film, comprising the following steps:

[0008] (1) mixing aramid nanofiber sol and halogenated alkane and then covalently cross-linking to obtain pre-cross-linked ANF;

[0009] (2) subjecting the pre-crosslinked ANF obtained in step (1) to a scraping treatment, and then subjecting the pre-crosslinked ANF to an acid coagulation bath and a water bath treatment to obtain an ANF wet gel film;

[0010] (3) Solvent replacement and drying of the ANF wet gel membrane obtained in step (2) to obtain a covalently cross-linked aramid nanofiber aerogel membrane.

[0011] Preferably, in step (1), the amount of the halogenated alkane used is 3-5% of the mass of the aramid nanofiber sol.

[0012] Preferably, in step (1), the temperature of the covalent cross-linking is 26° C. and the time is 2 to 6 minutes.

[0013] Preferably, in step (2), the height of the scraper used for the film scraping treatment is 0.5 mm, 1 mm or 1.5 mm, and the speed of the scraper is 1000 mm·min -1 .

[0014] Preferably, in step (2), the acid coagulation bath comprises formic acid, and the treatment time in the acid coagulation bath is 30 to 120 seconds.

[0015] Preferably, in step (2), the treatment time in the water bath is 12 hours.

[0016] Preferably, in step (3), the displacing agent used for the solvent replacement is tert-butyl alcohol.

[0017] Preferably, in step (3), the drying is freeze-drying; the freeze-drying temperature is -20°C and the time is 3 hours.

[0018] The present invention provides a covalently cross-linked aramid nanofiber aerogel membrane prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides the use of the covalently cross-linked aramid nanofiber aerogel film described in the above technical solution in thermal insulation materials and heat preservation materials.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] The mechanical properties of the CCAAM (covalently cross-linked aramid nanofiber aerogel membrane) prepared by the present invention are effectively improved. The nanofibers formed by cross-linking are stacked to form a dense pore wall, which improves the breaking strength to 13.14 MPa. The multi-level pore nanofiber skeleton honeycomb enables it to have more deformation ability, and the strain is improved to a maximum of 22.4%. At the same time, the cross-linked aerogel membrane is effectively toughened, and the fracture energy is as high as 181.833 MJ·m -3 , which is 2.2 times that of ANFAM.

[0022] The CCAAM prepared by the present invention has excellent flexibility, a bending strength as low as 0.019 MPa, and a bending stress recovery of 93.47% after 100 cycles, showing good bending fatigue resistance.

[0023] The CCAAM prepared by the present invention has excellent thermal stability, a thermal decomposition temperature as high as 533.9°C, and a low thermal conductivity (0.035 W·m -1 ·K -1 ) and excellent thermal insulation performance, it has good prospects in thermal insulation applications in high-temperature and complex scenes. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0025] Figure 1 Schematic diagram of the preparation process of the covalently cross-linked aramid nanofiber aerogel membrane in an embodiment of the present invention;

[0026] Figure 2 The load-bearing diagram (a), flexibility diagram (b), drape diagram (c), the actual diagram placed on foxtail grass (d), and the actual diagram attached and hung on the gear surface (e) of the CCAAM prepared in Example 1;

[0027] Figure 3 TEM images and diameter distribution graphs of the ANF sol in step (1) and the ANF-DBH sol in step (2) of Example 1, wherein a is the TEM image of the ANF sol, b is the TEM image of the ANF-DBH sol, c is the diameter distribution graph of the ANF sol, and d is the diameter distribution graph of the ANF-DBH sol;

[0028] Figure 4 Environmental scanning electron microscopy images of the ANF wet gel (a1, a2) in step (2) of comparative example 1 and the CCAAM wet gel (b1, b2) in step (3) of example 1 at different magnifications;

[0029] Figure 5The cross-sectional SEM images of the CCAAM prepared in Example 1 at different magnifications;

[0030] Figure 6 FTIR spectra of DBH, ANFAM prepared in Comparative Example 1, and CCAAM prepared in Example 1;

[0031] Figure 7 The XPS full spectra of ANFAM prepared in Comparative Example 1 and CCAAM prepared in Example 1 (a), and the C1s deconvoluted integrated peaks of ANFAM (b) and CCAAM (c);

[0032] Figure 8 XRD spectra of PPTA (aramid staple fiber), ANFAM prepared in Comparative Example 1, and CCAAM prepared in Example 1;

[0033] Fig. 9 The FTIR spectrum (a) of Example 2 step (2) after adding DBH changes with time and the FTIR spectrum (b) of Example 2 step (3) after immersing the liquid film in a formic acid coagulation bath changes with time;

[0034] Fig.10 The Raman spectra of the liquid film after being immersed in a formic acid coagulation bath in step (3) of Example 2 and in step (2) of Comparative Example 1;

[0035] Fig.11 The internal structure SEM images of ANFAM (a) in Comparative Example 1, CCAAM-3 (b) in Example 3, and CCAAM-6 (c) in Example 6;

[0036] Fig.12 The optical graph of the fluidity of the ANF-DBH sol in Examples 3 and 6 (a), the logarithmic-logarithmic graph of the apparent viscosity of the ANF sol as a function of the shear rate (b) and the ANF sol in Examples 7 to 9 25 Rheological properties of DBH sol (c);

[0037] Fig.13 The nitrogen adsorption-desorption curves (a) and pore size distributions (b) of ANFAM in Comparative Example 1 and CCAAM-3, CCAAM-4, CCAAM-5, and CCAAM-6 in Examples 3 to 6;

[0038] Fig.14 SEM images of CCAAM-3 (a1-a3), CCAAM-4 (b1-b3), CCAAM-5 (c1-c3) and CCAAM-6 (d1-d3) in Examples 3 to 6;

[0039] Fig.15The tensile stress-strain curves (a), toughness bar graph (b), breaking strength bar graph (c) and breaking elongation bar graph (d) of the CCAAM prepared in Examples 3 to 6 and the ANFAM prepared in Comparative Example 1;

[0040] Fig.16 The SEM images of the tensile fracture cross-sectional morphology of the CCAAM prepared in Examples 3 to 6 and the ANFAM prepared in Comparative Example 1;

[0041] Fig.17 The figures are a bending stress comparison diagram of ANFAM in comparative example 1 and CCAAM in example 1 (a), a bending stress-strain curve of CCAAMC in examples 3 to 6 (b), a cyclic bending stress-strain curve of CCAAM-6 in example 6 (c), and a stress-time curve of CCAAM-6 in example 6 (d);

[0042] Fig.18 TG and DTG curves of ANFAM in Comparative Example 1 and CCAAM in Example 1;

[0043] Fig.19 The thermal conductivity (a) and the heating stage temperature rise curve (b) of ANFAM in comparative example 1 and CCAAM in examples 3 to 6;

[0044] Fig. 20 200°C heating and cooling curves of ANFAM in Comparative Example 1 and CCAAM in Example 1;

[0045] Fig.21 This is a comparison chart of infrared thermal imaging of ice melting on the hot stage of CCAAM in Example 1. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] The room temperature in the embodiments of the present invention refers to "25±2°C".

[0049] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0050] In the following examples, aramid staple fiber (PPTA) was purchased from Teijin Ltd. of Japan, potassium hydroxide (KOH, analytical grade) was purchased from Tianjin Komeo Chemical Reagent Co., Ltd., dimethyl sulfoxide (DMSO, analytical grade) was purchased from Tianjin Komeo Chemical Reagent Co., Ltd., tert-butyl alcohol (analytical grade) was purchased from Tianjin Yongda Chemical Reagent Co., Ltd., 1,6-dibromohexane (DBH, analytical grade) was purchased from Aladdin Reagent Co., Ltd., formic acid (analytical grade) was purchased from Aladdin Reagent Co., Ltd., and deionized water was homemade in the laboratory.

[0051] Example 1

[0052] Preparation process of covalently cross-linked aramid nanofiber aerogel membrane:

[0053] (1) Preparation of aramid nanofibers: 1.5 g KOH was dissolved in 20 mL deionized water to obtain a KOH aqueous solution; 1 g aramid staple fiber was placed in 500 mL DMSO, and then the KOH aqueous solution was added and heated in a water bath at 60 °C for 4 h to obtain a KOH solution with a concentration of 20 mg mL -1 of ANF sol.

[0054] (2) Covalent crosslinking of aramid nanofibers: The ANF sol prepared in step (1) was poured into a beaker, stirred with a magnetic rotor, and then DBH was added to carry out covalent crosslinking at 26°C for 3 min. The amount of DBH used was 2.0% of the mass of the ANF sol to obtain an ANF-DBH sol.

[0055] (3) Preparation of wet gel film: Pour the ANF-DBH sol prepared in step (2) evenly onto a glass plate, adjust the scraper height to 1.5 mm, and control the scraper speed to 1000 mm min. -1 , the sol was evenly spread to obtain a liquid film; the liquid film and the glass plate were immersed in a 200mL formic acid coagulation bath, and after 1 minute, it was completely whitened to form a wet gel film, and then immersed in 1000mL deionized water for 12 hours and washed several times to obtain a CCAAM wet gel.

[0056] (4) Solvent replacement and freeze drying: The CCAAM wet gel obtained in step (3) was soaked in tert-butyl alcohol for multiple times to completely replace the water in the wet gel membrane, and then freeze-dried at -20°C for 3h to obtain a covalently cross-linked aramid nanofiber aerogel membrane CCAAM.

[0057] Comparative Example 1

[0058] (1) Preparation of aramid nanofibers: 1.5 g KOH was dissolved in 20 mL deionized water to obtain a KOH aqueous solution; 1 g aramid staple fiber was placed in 500 mL DMSO, and then the KOH aqueous solution was added and heated in a water bath at 60 °C for 4 h to obtain a KOH solution with a concentration of 20 mg mL-1 of ANF sol.

[0059] (2) Preparation of wet gel film: Pour the ANFs sol prepared in step (1) evenly onto a glass plate, adjust the scraper height to 1.5 mm, and control the scraper speed to 1000 mm min. -1 , the sol was evenly spread to obtain a liquid film; the liquid film and the glass plate were immersed in a 200mL formic acid coagulation bath, and after 1 minute, it was completely whitened to form a wet gel film, and then immersed in 1000mL deionized water for 12 hours and washed several times to obtain ANF wet gel.

[0060] (3) Solvent replacement and freeze drying: The ANF wet gel obtained in step (2) is soaked in tert-butyl alcohol for multiple times to completely replace the water in the wet gel membrane, and then freeze-dried at -20°C for 3 hours to obtain a covalently cross-linked aramid nanofiber aerogel membrane ANFAM.

[0061] Figure 1 Schematic diagram of the preparation process of the covalently cross-linked aramid nanofiber aerogel membrane in Example 1. Figure 1 It can be seen that the preparation process of covalently cross-linked aramid nanofiber aerogel membrane is divided into five steps: preparation of ANFs sol, covalent cross-linking of ANFs sol, blade coating, solvent replacement, and freeze drying.

[0062] Figure 2 The load-bearing diagram (a), flexibility diagram (b), drape diagram (c), the actual image placed on foxtail grass (d), and the actual image attached and draped to the surface of a gear (e) of the CCAAM prepared in Example 1. Figure 2 It can be seen that CCAAM can pull up a weight of up to 500g, can be tied into knots arbitrarily, and has excellent drapability when gently picked up with tweezers. Its thickness is 0.35mm and its density is about 18mg·cm -3 , can be placed on foxtail grass. When facing complex objects such as gears, it can also easily adhere to and hang on the surface of the gear, showing the characteristics of ultra-light, ultra-soft and ultra-strong.

[0063] Figure 3 TEM images and diameter distribution graphs of the ANF sol in step (1) and the ANF-DBH sol in step (2) of Example 1, wherein a is the TEM image of the ANF sol, b is the TEM image of the ANF-DBH sol, c is the diameter distribution graph of the ANF sol, and d is the diameter distribution graph of the ANF-DBH sol. Figure 3a It can be seen that the dissolution of aramid staple fibers in the KOH / DMSO system causes the macroscopic fibers to gradually split into nanoscale. This process occurs by extracting mobile hydrogen from the -NH groups and greatly reducing the strength of hydrogen bonds between polymer chains while increasing electrostatic repulsion. This cleavage is limited and does not drop to the level of a single polymer chain. The complete decomposition of the fibers into separate chains is to offset the hydrophobic attraction and π-π stacking on the polymer backbone. Figure 3 c It can be seen that the diameter of ANF sol is 5-40nm. Figure 3 b and Figure 3 It can be seen from the figure that after adding DBH, the halogenated alkanes replace a part of the proton donors and combine with the deprotonated amide groups in the aramid molecular chain in advance, which leads to the self-assembly of the aramid nanofibers under the traction of covalent bonds, and the diameter increases to between 50-350nm.

[0064] Figure 4 The environmental scanning electron microscope images of the ANF wet gel (a1, a2) in step (2) of comparative example 1 and the CCAAM wet gel (b1, b2) in step (3) of example 1 at different magnifications, wherein a1 and a2 are ANF wet gels, and b1 and b2 are CCAAM wet gels. Figure 4 It can be seen that the structure of ANF wet gel is relatively uniform ( Figure 4 a1 and 4a2), while the presence of micropores can be clearly observed in CCAAM wet gel ( Figure 4 b1 and Figure 4 The darker part in b2) is different from the micropores obtained by the ice template method, indicating that the multi-level structure at this time is formed by the self-assembly of ANF during the reprotonation process, rather than being formed by the influence of ice crystals during the freeze-drying process.

[0065] Figure 5 The cross-sectional SEM images of the CCAAM prepared in Example 1 at different magnifications are shown in FIG. Figure 5 It can be seen that the CCAAM obtained after freeze-drying retains the multi-level pore structure formed by the self-assembly of ANF under wet gel, and the nanofiber skeleton honeycomb inside it has abundant pores. The molecular chains of the aramid nanofibers reduced by high concentration protons are connected and strengthened by a large number of hydrogen bonds to form a dense cortical structure, which improves the strength of the membrane while also weakening the flexibility of the aerogel membrane to a certain extent. The multi-level pore layer of CCAAM provides a structural basis for its higher deformation ability.

[0066] The chemical group structures of DBH, ANFAM prepared in Comparative Example 1, and CCAAM prepared in Example 1 were characterized using a Fourier transform infrared spectrometer (FTIR) with a scanning range of 4000-400 cm -1 , the results are as follows Figure 6 As shown. Figure 6 It can be seen that in the FTIR spectrum of ANFAM, 3420 cm -1 、1649cm -1 、1541cm -1 、1514cm -1 、1310cm -1 and 1017cm -1 The peaks at 2853 cm-1 belong to NH stretching, C=O stretching, NH deformation and CN stretching vibration coupling mode, C=C stretching, Ph-N stretching and in-plane CH mixing vibration. At the same time, these characteristic peaks can also be observed in the FTIR spectrum of CCAAM, indicating that these polar functional groups are also retained in CCAAM. In addition, CCAAM has a peak at 2853 cm-1. -1 、2924cm -1 and 2961cm -1 There is a strong peak corresponding to the alkyl peak on DBH, indicating that DBH is successfully grafted onto ANF.

[0067] Figure 7 The XPS full spectra of ANFAM prepared in Comparative Example 1 and CCAAM prepared in Example 1 (a), and the deconvoluted C1s peaks of ANFAM (b) and CCAAM (c). Figure 7 a It can be seen that all films are composed of C, N and O elements. Figure 7 bc It can be seen that the C1s of CCAAM shows a higher CC peak content, which is due to the introduction of multi-carbon long chains in DBH. The binding energies of CCAAM are 284.6 eV, 285.6 eV, 287.8 eV, and 290.7 eV, respectively, attributed to the interactions of CC, CN, C=O, and COOH.

[0068] The percentage contents of CC, CN, NC=O, and COOH in the ANFAM prepared in Comparative Example 1 and the CCAAM prepared in Example 1 are shown in Table 1.

[0069] Table 1 Percentage content of CC, CN, NC=O, COOH in ANFAM and CCAAM

[0070] sample CC CN NC=O COOH ANFAM 62.83% 3.88% 8.22% 4.34% CCAAM 63.63% 6.37% 7.84% 0.75%

[0071] It can be clearly seen from Table 1 that compared with ANFAM, the CC and CN contents in CCAAM have increased, and the COOH content has decreased significantly. This is because during the cross-linking process, DBH removes the bilateral halogen Br and combines with the amide group on the aramid nanofiber molecular chain to produce covalent cross-linking and generate CN bonds, which weakens some hydrogen bonds during the re-protonation process, thereby reducing the proportion of COOH. The increase in the CC group content also assisted in proving the successful access to the covalent bond long carbon chain. The above shows that the introduction of DBH was successful and a covalent cross-linking reaction was carried out.

[0072] The crystallinity of PPTA (aramid staple fiber), ANFAM prepared in Comparative Example 1 and CCAAM prepared in Example 1 was characterized by X-ray diffractometer (XRD). Figure 8 .Depend on Figure 8 It can be seen that both PPTA and ANFAM show obvious 2θ characteristic diffraction peaks at 20.7°, 23°, and 28.5°, corresponding to the (110), (200), and (004) lattice planes, but the characteristic diffraction peak of CCAAM is weaker, indicating that the crystallinity decreases after covalent cross-linking with DBH, which may be due to the destruction of hydrogen bonds between ANF chains.

[0073] Example 2

[0074] Preparation process of covalently cross-linked aramid nanofiber aerogel membrane:

[0075] (1) Prepare the mixture with a concentration of 15 mg mL according to step (1) of Example 1. -1 of ANF sol.

[0076] (2) Pour 20 mL of the ANFs sol prepared in step (1) into a beaker, add a magnetic rotor for stirring, and then add 2 μL of DBH for covalent crosslinking at (26)°C. The crosslinking time is 0-270 s (0-4.5 min) to obtain an ANF-DBH sol.

[0077] (3) Preparation of wet gel film: Pour the ANF-DBH sol prepared in step (2) evenly onto a glass plate, adjust the scraper height to 1.5 mm, and control the scraper speed to 1000 mm min. -1 The sol is evenly spread to obtain a liquid film; the liquid film and the glass plate are immersed in a 200 mL formic acid coagulation bath for 300 to 1000 s (based on the 270 s in step (2)) until it completely turns white and forms a wet gel film, and then immersed in 1000 mL deionized water for 12 h and washed several times to obtain a CCAAM wet gel.

[0078] (4) Solvent replacement and freeze drying: The CCAAM wet gel obtained in step (3) was soaked in tert-butyl alcohol for multiple times to completely replace the water in the wet gel membrane, and then freeze-dried at -20°C for 3h to obtain a covalently cross-linked aramid nanofiber aerogel membrane CCAAM.

[0079] After adding DBH in step (2) of Example 2, in-situ infrared spectroscopy was immediately used to scan for real-time detection with a scanning range of 4000 cm -1 Up to 400cm -1 , resolution 4cm -1 , the test results are shown in Fig. 9 a. Then, in step (3), the liquid film is immersed in a formic acid coagulation bath and the timing is continued. When the peak intensity and peak shape in the spectrum no longer change, the detection is stopped and the scanning time of each spectrum line is recorded. The results are shown in Fig. 9 b.

[0080] Depend on Fig. 9 a It can be seen that before adding DBH, the typical vibration peak of ANF sol could not be detected. Then, 2 μL of DBH was added to the sol. At 30 s, 1246 cm -1 The CN vibration peak at 2853 cm -1 、2924cm -1 and 2961cm -1 The CH2 vibration at 3420 cm was also detected, indicating that covalent cross-linking has begun. The sol was scanned every 30 s, and it can be seen that with the increase of time, the CH2 and CN peak intensities continued to increase until 180 s, when the peak intensities of the two peaks no longer changed significantly, indicating that the added DBH was completely grafted onto the ANF long chain, proving that the cross-linking reaction process was completed. It is worth noting that at this time, the peak at 3420 cm -1 The NH stretching vibration at the position did not appear, indicating that the covalent cross-linking reaction did not affect the reprotonation process of the ANF sol. The cross-linked sol was then treated with an acid coagulation bath for protonation reduction. The characterization results are shown in Fig. 9 As shown in b, at 3420cm -1 and 1642cm -1 The stretching vibration peaks of NH and C=O of ANF can be observed at the 480th second. The characteristic peaks gradually appear and become more significant with the passage of time, indicating that under the acidic coagulation bath conditions, the amide group of ANF is gradually reduced and the structure is gradually complete, while the characteristic peak of CH2 has basically no change, indicating that during the reprotonation of ANF, the covalent cross-linking reaction no longer proceeds, and after 480 seconds, the peak intensity basically no longer changes, indicating that the reprotonation process of ANF is basically completed.

[0081] In-situ Raman spectroscopy was used to characterize the reprotonation reduction process after the liquid membrane was immersed in the formic acid coagulation bath in step (3) of Example 2 and in step (2) of Comparative Example 1. The results are as follows: Fig.10 shown. Fig.10 a medium 1350cm -1 The peak at 1570cm is the vibration peak of the aliphatic multi-carbon long chain. It was detected at 30s. At this time, some DBH has removed the halogen Br to attack the CH part of the amide group and combined to form CN. After adding a proton donor for reduction, the electron cloud density changes when the deprotonated ANF molecular chain changes from a negatively charged state to an uncharged state, and the benzene ring skeleton changes from asymmetric vibration to symmetric vibration, which makes Raman activity appear. 1570cm -1 The vibration absorption coupling peak intensity of CN and NH in the amide I band appears and increases, and the amide II band is 1650cm -1 Strength enhancement ( Fig.10 b). Compare with 1570cm at 300s at the same time -1 In the amide I band, the peak intensity of ANF-DBH is significantly higher than that of ANF due to the covalent cross-linking reaction. This phenomenon indicates that the introduction of DBH causes ANF to be affected by covalent bonds during proton reduction, and cooperates with hydrogen bonds to restore the complete molecular structure.

[0082] Embodiments 3 to 6

[0083] The difference from Example 1 is that in step (2), the cross-linking time is 3 min (Example 3, denoted as CCAAM-3), 4 min (Example 4, denoted as CCAAM-4), 5 min (Example 5, denoted as CCAAM-5), and 6 min (Example 6, denoted as CCAAM-6).

[0084] Embodiments 7 to 9

[0085] The difference from Example 1 is that in step (2), the amount of DBH used is 3% of the mass of the ANF sol (Example 7, denoted as ANF 25 DBH-3), 4% (Example 8, denoted as ANF 25 DBH-4), 5% (Example 9, denoted as ANF 25 DBH-5).

[0086] Fig.11 The internal structure SEM images of ANFAM (a) in Comparative Example 1, CCAAM-3 (b) in Example 3, and CCAAM-6 (c) in Example 6 are shown in FIG. Fig.11It can be seen that the uncross-linked ANFAM is a uniform network composed of nanofibers, CCAAM-3 is a multi-level porous nanofiber honeycomb skeleton with micron-sized pores, and the pore walls are composed of stacked nanofibers. Due to excessive cross-linking, the nanofibers of CCAAM-6 gradually aggregate into a lamellar structure, and the nanopores are retained to a certain extent.

[0087] Fig.12 The optical graph of the fluidity of the ANF-DBH sol in Examples 3 and 6 (a), the logarithmic-logarithmic graph of the apparent viscosity of the ANF sol as a function of the shear rate (b) and the ANF sol in Examples 7 to 9 25 Rheological properties of DBH sol (c). Fig.12 It can be seen from a that after adding 3% DBH to the ANF sol, the fluidity of the sol decreased after 3 minutes and began to solidify gradually. At 6 minutes, the dispersion was completely gelled. This phenomenon also shows that DBH can be used as a cross-linking agent to form covalent alkane bonds at the anionic sites. Fig.12 b It can be seen that the ANF sol shows obvious shear thinning behavior, in which the viscosity depends on the expected shear rate. When the shear rate changes, the viscosity of the sol gradually decreases from 255310mPa·s to 5860mPa·s, and the yield stress is 586.01Pa. Then different contents of DBH were added to it, and the shear rate was controlled to be constant at 100 1 / s. The change of viscosity over time was observed, and the results are shown in Fig.12 c. Fig.12 c The results show that after adding DBH, the viscosity of the sol decreases to a certain extent because DBH is a colorless and transparent liquid. However, as the covalent cross-linking reaction proceeds, the viscosity increases significantly, and the increasing trend slows down with the increase in the amount of DBH added.

[0088] The specific surface area and pore size distribution of ANFAM, CCAAM-3, CCAAM-4, CCAAM-5 and CCAAM-6 were tested by using a fully automatic specific surface and porosity analyzer (BET) and determined by gas adsorption method. About 30 mg of membrane sample was weighed, torn into small pieces, degassed for 3 hours under N2 atmosphere and 200°C, and then tested by adsorbing N2 at 70K to obtain the adsorption-desorption curve of the sample, calculate the specific surface area of ​​the sample, and calculate the pore size distribution of the sample using the BJH method. The results are shown in Fig.13 .Depend on Fig.13a It can be seen that when the relative pressure is low, the first half of the nitrogen adsorption-desorption curves of all materials are flat, indicating that the gas is mainly filled in the micropores. As the relative pressure increases, the second half of the curve shows that the adsorption-desorption curves do not overlap, which is attributed to the adsorption hysteresis caused by the capillary condensation effect in the mesopores and macropores. The typical type IV isotherm characteristics shown in the nitrogen adsorption-desorption curves indicate the existence of mesopores in the material, and the adsorption amount gradually increases with the increase of partial pressure. At the same time, the adsorption isotherm is highly consistent with the H4 hysteresis loop characteristics, further confirming the existence of a large number of mesopores and macropores in the aerogel structure. Fig.13 b It can be seen that the pore size distribution of ANFAM and CCAAM is mainly concentrated in the range of 2-100nm. It is worth noting that in the pore size range of 2-20nm, the pore content shows a trend of gradually decreasing with the extension of crosslinking time. The occurrence of this phenomenon can be attributed to the stacking and aggregation effect of nanofibers during the crosslinking process, which leads to the gradual densification of the aerogel structure.

[0089] Fig.14 SEM images of CCAAM-3 (a1-a3), CCAAM-4 (b1-b3), CCAAM-5 (c1-c3) and CCAAM-6 (d1-d3), where a1, a2, a3 are CCAAM-3, b1, b2, b3 are CCAAM-4, c1, c2, c3 are CCAAM-5, and d1, d2, d3 are CCAAM-6. Fig.14 It can be seen from a and 14b that the internal structures of CCAAM-3 and CCAAM-4 after structural regulation have many interconnected honeycomb skeleton network structures composed of nanofibers. Fig.14 c and Fig.14 d It can be seen that CCAAM-5 and CCAAM-6 have a lamellar framework structure. Among them, the lamellar framework of CCAAM-5 aerogel is mainly composed of densely stacked nanofibers, and there is a nanofiber network structure between the lamellar frameworks. For CCAAM-6, the nanofibers are fused together and are almost invisible in the lamellar framework. There are few incomplete lamellar structures formed by the combination of nanofibers, which reflects that the frameworks of CCAAM-5 and CCAAM-6 are denser than those of CCAAM-3 and CCAAM-4. The difference in the internal structure of different aerogels is mainly due to the different cross-linking time, which leads to a reduction in the number of amide groups occupied on the ANFs molecular chain, which in turn affects the protonation ability and the ability to form hydrogen bonds, affecting the dispersion and binding force of ANFs during solvent exchange.

[0090] Fig.15The tensile stress-strain curves (a), toughness bar graph (b), breaking strength bar graph (c), and breaking elongation bar graph (d) of the CCAAM prepared in Examples 3 to 6 and the ANFAM prepared in Comparative Example 1. The test method is: cut a sample of 1 cm × 3 cm in size, the clamp distance is 2 cm, and the stretching speed is 5 mm·min -1 , until the sample breaks, each group of samples is measured three times and the average value is taken. Fig.15 It can be seen that the tensile strength of ANFAM is 9.72MPa, while the fracture strength of CCAAM after cross-linking is positively correlated with the cross-linking time. The fracture strength of CCAAM-6 reaches an astonishing 13.14MPa. It is worth noting that while the strength is improved, the strain of CCAAM is also effectively improved. The strain of CCAAM-6 is 8.95% higher than that of ANFAM. At the same time, the fracture energy of CCAAM-6 is as high as 181.833MJ / m 3 , which is 2.2 times that of ANFAM.

[0091] Fig.16 The SEM images of the tensile fracture cross-section morphology of the CCAAM prepared in Examples 3 to 6 and the ANFAM prepared in Comparative Example 1 are shown. Fig.16 It can be clearly observed that the fracture surface of ANFAM is relatively flat and smooth, which is due to the fracture caused by the uniform nanofiber network inside. As the crosslinking time of CCAAM increases, the fracture interface is accompanied by the slip of the fiber layer, indicating that the original micropores have undergone a large amount of deformation. The micropore walls are composed of crosslinked nanofibers, which provide strong support and are accompanied by the pull-out of the fiber sheet. Under the synergistic effect of the two, the mechanical strength and toughness of CCAAM are effectively improved. The results show that DBH, as a crosslinking agent, is easy to form covalent bonds with ANF and has strong interfacial adhesion. Compared with the highly ordered hydrogen bonds in ANF, the high-energy covalent bonds can effectively transmit interfacial stress, thereby improving the mechanical strength and toughness of the aerogel film.

[0092] The bending performance of ANFAM and CCAAM was tested. The sample size was 1 cm × 6 cm, the clamping distance was 4 cm, and the film was clamped vertically in the fixture. The upper fixture was moved downward to bend the film. The clamping distance was 2.8 cm, corresponding to a compression displacement of 70%, and the speed was 14 mm min. -1 , the results are shown in Fig.17 .

[0093] Fig.17 The bending stress comparison diagram of ANFAM in comparative example 1 and CCAAM in example 1 (a), the bending stress-strain curve of CCAAMC in examples 3 to 6 (b), the cyclic bending stress-strain curve of CCAAM-6 in example 6 (c), and the stress-time curve of CCAAM-6 in example 6 (d). Fig.17As can be seen from a, the peak bending strength of ANFAM reaches 0.64MPa, while that of CCAAM is only 0.077MPa, which can easily be bent at 70% strain. Five bending tests were conducted on CCAAM with different crosslinking times, and the results are shown in Fig.17 b, it can be seen that CCAAM with different cross-linking times all showed extremely low bending stress, indicating that it has good flexibility. In order to verify the fatigue resistance of multiple bending, CCAAM-6 was subjected to 100 bending cycle tests, and the results are shown in Fig.17 c and Fig.17 d. It can be seen that after 100 cycles, the bending recovery curve of CCAAM-6 remains closed, and compared with the first bending stress after 100 cycles, the stress only decreases from 0.046MPa to 0.043MPa, with a retention rate of 93.47%, indicating that CCAAM has good bending fatigue resistance.

[0094] The thermal stability of ANFAM and CCAAM was analyzed. The samples were dried in an oven at 60°C for 3 hours to remove moisture and ensure measurement accuracy. About 10 mg was weighed and placed in an alumina crucible. The test conditions were nitrogen atmosphere, temperature from room temperature to 800°C, and the heating rate was 10°C min. -1 , and obtain the thermogravimetric (TG) curve of the sample.

[0095] Fig.18 TG and DTG curves of ANFAM in Comparative Example 1 and CCAAM in Example 1. Fig.18 It can be seen that the thermal stability of ANFAM and CCAAM is similar, and both aerogel films show thermal stability at high temperatures, inheriting the thermal properties of PPTA. However, since covalent cross-linking weakens some hydrogen bonds, resulting in a decrease in the crystallinity of CCAAM, the residual mass at 800°C is slightly lower than that of ANFAM, but only 1.12%, which is almost negligible in actual use, and can still maintain good thermal stability.

[0096] The TG data of ANFAM in Comparative Example 1 and CCAAM in Example 1 are summarized in Table 2.

[0097] Table 2 Summary of TG data of ANFAM and CCAAM

[0098] sample 800℃ Residue(%) Td(℃) <![CDATA[Td 20 %(℃)]]> ANFAM 41.28 527.7 560.6 CCAAM 40.16 533.9 565.0

[0099] Fig.19 The thermal conductivity (a) and the heating curve (b) of the ANFAM in comparative example 1 and the CCAAM in examples 3 to 6 are shown in FIG. Fig.19 It can be seen from a that the thermal conductivity of the five materials ranges from 0.034 to 0.040 W·m -1 K-1 This value range is comparable to that of commercial thermal insulation aerogel materials widely sold on the market, and is fully within the standard range of thermal conductivity of thermal insulation materials. It is worth noting that the increase in cross-linking time has a significant effect on the thermal conductivity of CCAAM. The core mechanism of this phenomenon is that the increase in cross-linking time causes the original nanofiber network structure to transform into a layered porous structure. This structural change directly leads to an increase in the proportion of solid-phase heat conduction, which is ultimately reflected in an increase in thermal conductivity. Fig.19 b It can be clearly observed that as the cross-linking time increases, the temperature difference between the CCAAM surface and the hot stage gradually decreases, from 19.7°C for CCAAM-3 to 10°C for CCAAM-6, which is consistent with the increasing trend of thermal conductivity. But overall, the aerogel film after covalent cross-linking still maintains good thermal insulation performance.

[0100] The ANFAM in Comparative Example 1 and the CCAAM in Example 1 were cut to a thickness of 2.5 mm, and their thermal insulation properties at high temperatures were tested. The temperature-time curves were recorded by thermocouples. The results are shown in FIG. Fig. 20 As shown. Fig. 20 It can be seen that the temperature difference between ANFAM and CCAAM is much lower than the heating temperature of the hot stage. The temperature difference of ANFAM is slightly higher than that of CCAAM, but the difference is only 8.91 °C. The dense cortex and nanofiber network of ANFAM block thermal radiation and convection, thereby hindering the diffusion of heat to the surrounding air and delaying heat loss. The micron-sized pores in CCAAM cannot limit the movement of hot air molecules at high temperatures, resulting in a partial increase in gas-phase heat conduction.

[0101] The CCAAM in Example 1 with a thickness of 1 mm was placed on the surface of a hot table, covered with a layer of plastic wrap and then placed with ice cubes. The temperature of the heating table was raised to 40°C, and the side was photographed with an infrared thermal imager to record the temperature change and observe the melting height of the ice cubes. The blank control group was a glass plate. The results are shown in FIG. Fig.21 .from Fig.21 It can be seen that the ice cubes in the blank control group completely melted in 300s, while the ice cubes on the CCAAM melted only 1 / 4 at this time, which effectively delayed the melting time, indicating that it has good thermal insulation effect.

[0102] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a covalently cross-linked aramid nanofiber aerogel membrane, characterized in that: The following steps are involved: (1) mixing aramid nanofiber sol and halogenated alkane and then covalently cross-linking to obtain pre-cross-linked ANF; (2) subjecting the pre-crosslinked ANF obtained in step (1) to a scraping treatment, and then subjecting the pre-crosslinked ANF to an acid coagulation bath and a water bath treatment to obtain an ANF wet gel film; (3) Solvent replacement and drying of the ANF wet gel membrane obtained in step (2) to obtain a covalently cross-linked aramid nanofiber aerogel membrane.

2. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (1), the amount of the halogenated alkane used is 3-5% of the mass of the aramid nanofiber sol.

3. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (1), the temperature of the covalent cross-linking is 26° C. and the time is 2 to 6 minutes.

4. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (2), the height of the scraper used for the film scraping treatment is 0.5 mm, 1 mm or 1.5 mm, and the speed of the scraper is 1000 mm·min -1 .

5. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (2), the acid coagulation bath includes formic acid, and the treatment time in the acid coagulation bath is 30 to 120 seconds.

6. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (2), the treatment time in the water bath is 12 hours.

7. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (3), the solvent replacement agent used is tert-butyl alcohol.

8. The method for preparing the covalently cross-linked aramid nanofiber aerogel membrane according to claim 1, characterized in that: In step (3), the drying is freeze drying; the freeze drying temperature is -20°C and the time is 3 hours.

9. A covalently cross-linked aramid nanofiber aerogel membrane prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the covalently cross-linked aramid nanofiber aerogel film according to claim 9 in thermal insulation materials and heat preservation materials.